Natural Products Mediated Targeting of Virally Infected Cancer - Iram Fatima; Sobia Kanwal; Tariq Mahmood (SAGE Publishing, 2019)
The role of viral infection in developing cancer was determined in the start of 20th century. Until now, 8 different virus-associated cancers have been discovered and most of them progressed in immunosuppressed individuals. The aim of the present study is to look into the benefits of natural products in treating virally infected cancers. The study focuses on bioactive compounds derived from natural sources. Numerous pharmaceutical agents have been identified from plants (vincristine, vinblastine, stilbenes, combretastatin, and silymarin), marine organisms (bryostatins, cephalostatin, ecteinascidins, didemnin, and dolastatin), insects (cantharidin, mastoparan, parectadial, and cecropins), and microorganisms (vancomycin, rhizoxin, ansamitocins, mitomycin, and rapamycin). Beside these, various compounds have been observed from fruits and vegetables which can be utilized in anticancer therapy. These include curcumin in turmeric, resveratrol in red grapes, S-allyl cysteine in allium, allicin in garlic, catechins in green tea, and β-carotene in carrots. The present study addresses various types of virally infected cancers, their mechanism of action, and the role of different cell surface molecules elicited during viral binding and entry into the target cell along with the anticancer drugs derived from natural products by targeting screening of bioactive compounds from natural sources.